Knowledge, perception, and attitude toward premarital screening among university students in Kurdistan region-Iraq. - Kochr A Mahmood; Govand S Sadraldeen; Samir M Othman; Nazar P Shabila; Abubakir M Saleh; Kameran H Ismail (Public Library of Science (PLoS), 2024)
Premarital screening programs are essential for identifying and providing counseling to couples at risk of transmitting genetic diseases or sexually transmitted infections. Despite their importance, university students' awareness and knowledge of premarital screening programs remain inadequate. This study aimed to evaluate the knowledge, perceptions, and attitudes of university students in the Kurdistan Region of Iraq regarding premarital screening programs. A cross-sectional survey involving 960 students was conducted from December 2023 to February 2024. The survey assessed participants' demographics, knowledge, perception, and attitudes toward PMSP using a structured questionnaire. Findings revealed that a significant portion of participants (39.4%) had poor knowledge of premarital screening programs, 35.9% had fair knowledge, and only 24.7% had good knowledge. Despite limited knowledge, there was strong support for premarital screening programs, with 83.1% agreeing on its importance and 78.8% recognizing the need for premarital awareness. Most participants (65.8%) believed premarital screening programs could reduce genetic diseases, and 65.6% thought it could lower sexually transmitted diseases' prevalence. Cultural acceptance of marrying relatives was notable, with 59.7% disagreeing with the preference for not marrying relatives. Married participants showed significantly higher knowledge and attitude scores compared to single participants. Gender differences were observed, with males having higher knowledge scores. There were no significant differences in perception and attitude scores based on gender or residential area. The study underscores the need for enhanced educational campaigns to improve premarital screening programs awareness and positively influence attitudes, especially targeting cultural aspects like accepting relative marriages. Comprehensive education and fostering positive attitudes toward premarital screening programs are vital for their broader acceptance and implementation.